Serology, isolation, and molecular detection of Leptospira spp. from the tissues and blood of rats captured in a wild animal preservation centre in Brazil - Paixao, Mirian dos Santos [UNESP]; Alves-Martin, Maria Fernanda [UNESP]; Tenorio, Michely da S. [UNESP]; Starke-Buzetti, Wilma A. [UNESP]; Alves, Maria Luana [UNESP]; Silva, Diogo Tiago da [UNESP]; Ferreira, Andrea Goncalves [UNESP]; Floro e Silva, Marina [UNESP]; Sousa, Ludo O.; Lucheis, Simone Baldini [UNESP] (Elsevier B.V., 2014)
To elucidate the occurrence and epidemiology of leptospirosis in rats cohabitating with forest animals, 13 rats were captured at seven locations of the Centre for the Conservation of Wild Fauna (CCWF) in Sao Paulo state, Brazil, and samples of their blood, liver, and kidneys were collected. The diagnostic techniques utilized were the microscopic agglutination test (MAT), polymerase chain reaction (PCR) for Leptospira spp., and cultures of rat kidneys and liver in Fletcher's medium. The MAT results showed that 13 (100%) of the samples were reactive to 12 serovars among the 29 Leptospira spp. tested, and the Australis and Tarassovi serovars were the most frequently identified serovars. To research the agent in fragments of the liver and kidney, 13 samples from each tissue were cultured in Fletcher's medium, and the results revealed seven positive samples (53.8%; three from the kidneys and four from the livers). The analysis of the blood samples by PCR for Leptospira spp. showed that six animals (46.1%) were positive, whereas the analysis of the organs (kidneys and liver) by PCR revealed that nine animals (69.2%) were positive, and the culture of the organs revealed four positive animals (30.8%). These results suggest that the presence of Leptospira spp. infection in rats at the study site and the knowledge of the serovars that exist in this environment are important for the epidemiological comprehension of the disease and for the identification of control measures that should be considered to reduce the risk of transmission of the disease through this animal reservoir. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Leptospirosis; Rats; Serology; Culture; PCR